An Analysis of Directive Acts Found in â€œThe Princess Switchâ€ Movie - Cindy Erika Damanik; Ambalegin Ambalegin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The aim of this descriptive qualitative research was to examine the various types of directive uttered by the characters in The Princess Switch movie. The data were collected from the characters' utterances of directive acts in the movie. The theory proposed Searle (1979) was used to analyze the types of directive acts. The observational method and non-participatory technique were employed to obtain the data. In addition, the data were evaluated using the pragmatic identity method and pragmatic competence- in equalizing technique. The results demonstrated that the characters in The Princess Switch movie delivered 20 utterances of directive acts. There were 9 data displayed asking, 3 data displayed requesting, 1 data displayed inviting, 3 data displayed advising, 3 data displayed permitting, and 1 data displayed commanding. The asking type of directive acts was the most common type as the characters in the Princess Switch regularly asking each other questions.Â